Comparison of the effects of perioperative fentanyl and morphine use on the short-term prognosis of patients with cardiac surgery in the ICU - Zhong, Jingtao; Sui, Runqian; Zi, Jie; Wang, Anbiao (Frontiers in Pharmacology, 2025)
AimThis study aimed to analyze the effects of perioperative morphine and fentanyl use on delirium, length of ICU stay, and in-hospital mortality after cardiac surgery.MethodsThis cohort study retrieved the data of 4,596 patients admitted to ICU after cardiac surgery in MIMIC-IV database from 2008 to 2019. The primary outcome was postoperative delirium. The secondary outcomes were length of ICU stay, and in-hospital mortality. To compare the effects of perioperative fentanyl and morphine use on postoperative delirium, length of ICU stay, and in-hospital mortality, univariate, two-way stepwise, as well as multivariable Logistic regression, linear regression, and Cox proportional hazards models was respectively used. Odd ratio (OR), β coefficient, hazard ratio (HR), and respective confidence interval (CI) were calculated. Subgroup analysis was conducted in terms of age, use of extracorporeal circulation, midazolam, dexmedetomidine or surgery type.ResultsIn total, the data of 4,596 patients were analyzed including 2,589 morphine user and 2007 fentanyl user. We found that the risk of postoperative delirium was reduced in patients with cardiac surgery undergoing perioperative morphine relative to perioperative fentanyl (OR = 0.62, 95%CI: 0.40–0.96). Perioperative morphine use was negatively correlated with the length of ICU stay in patients with cardiac surgery in comparison to patients with perioperative fentanyl use (β = −0.72, 95%CI: −1.06, −0.39). Relative to patients who had perioperative fentanyl, patients who had perioperative morphine were associated with reduced risk of in-hospital mortality in patients with cardiac surgery after adjusting for respective confounding factors (HR = 0.35, 95%CI: 0.13–0.91).ConclusionPerioperative morphine use was related to lower risk of delirium and in-hospital mortality as well as shortened length of ICU stay in these patients. The findings might offer a reference for perioperative anesthesia management in patients receiving cardiac surgery.